2018
DOI: 10.1186/s12940-017-0345-y
|View full text |Cite
|
Sign up to set email alerts
|

Hair product use, age at menarche and mammographic breast density in multiethnic urban women

Abstract: BackgroundSelect hair products contain endocrine disrupting chemicals (EDCs) that may affect breast cancer risk. We hypothesize that, if EDCs are related to breast cancer risk, then they may also affect two important breast cancer risk factors: age at menarche and mammographic breast density.MethodsIn two urban female cohorts (N = 248): 1) the New York site of the National Collaborative Perinatal Project and 2) the New York City Multiethnic Breast Cancer Project, we measured childhood and adult use of hair oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 37 publications
(60 reference statements)
1
65
0
Order By: Relevance
“…McDonald et al found that increases in EDCs have been implicated in early menarche [59]. However, their study investigated EDCs in hair oils and hair products [59], which are likely somewhat different from the EDCs found in oil and gas wastewater. However, if the mechanism affecting age at menarche is the EDCs as proposed, then the specific chemical should not matter as long as endocrine disruption is taking place [177].…”
Section: Impact Of Climate Change On Pollutant Release and Timing Ofmentioning
confidence: 93%
See 2 more Smart Citations
“…McDonald et al found that increases in EDCs have been implicated in early menarche [59]. However, their study investigated EDCs in hair oils and hair products [59], which are likely somewhat different from the EDCs found in oil and gas wastewater. However, if the mechanism affecting age at menarche is the EDCs as proposed, then the specific chemical should not matter as long as endocrine disruption is taking place [177].…”
Section: Impact Of Climate Change On Pollutant Release and Timing Ofmentioning
confidence: 93%
“…Another study investigating the effects of breast cancer incidence and atomic bomb survivors in Japan and its relationship to timing of menarche found that the breast cancer incidence due to radiation was high regardless of the stage of the breast's differentiation, indicating that radiation exposure itself maybe a breast carcinogen [58]. Exposure to endocrine-disrupting chemicals [59] and hair products [59], and in utero exposure to atrazine [60] were all associated with early menarche ( Figure 3A). On the other hand, in utero exposure to organochlorine did not appear to alter the timing of menarche [61].…”
Section: Toxins and Pollutantsmentioning
confidence: 98%
See 1 more Smart Citation
“…Early age at menarche is associated with an increased risk of breast cancer 25 26 . Thereafter, age at menarche (> 13 years compared with < 13 years) was not the risk factor when adjusted all the variables that there were differences in the single logistic regression analysis in our study.…”
Section: Discussionmentioning
confidence: 99%
“…After publication of the article [ 1 ], it was brought to our attention that a number in Table 1 is incorrect. The table quotes the number of children with Maternal Language Preference listed as “Other” as being “240 (0.7%)”.…”
Section: Correctionmentioning
confidence: 99%